2018
DOI: 10.1002/ep.12893
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of natural dolomite for efficient removal of lead and cadmium in aqueous systems

Abstract: Physicochemical characterization of naturally abundant carbonates has been undertaken to evaluate their potentialities in the removal of lead and cadmium ions in aqueous systems. Powdered dolomite samples, collected from the Jebel Rehach location, southern Tunisia, were used in their natural form for the removal of both cadmium and lead in aqueous conditions. The removal experiments were carried out in batch by mixing known amount of dolomite powder with a metal solution (lead or cadmium). The mixture was shak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…[27] Furthermore, the mean of S/N ratio was found to decrease with impingement angle, suggesting that the means of erosion rate increases with increased impingement angle. As observed from figures for hand layup and VRTM based composites, the erosion wear remained lowest for smaller impingement angles (30 ) and attained the highest values at 90 of impingement angle, indicating F I G U R E 9 Interaction plot of S/N ratio for hand layup technique brittle erosion behavior. Similar results were reported for polymer composites by Öztürk et al [27] and Barkoula et al, [41] where maximum erosion wear was observed at 90 of impingement angle.…”
Section: Taguchi Analysis For Erosion Wearmentioning
confidence: 73%
See 2 more Smart Citations
“…[27] Furthermore, the mean of S/N ratio was found to decrease with impingement angle, suggesting that the means of erosion rate increases with increased impingement angle. As observed from figures for hand layup and VRTM based composites, the erosion wear remained lowest for smaller impingement angles (30 ) and attained the highest values at 90 of impingement angle, indicating F I G U R E 9 Interaction plot of S/N ratio for hand layup technique brittle erosion behavior. Similar results were reported for polymer composites by Öztürk et al [27] and Barkoula et al, [41] where maximum erosion wear was observed at 90 of impingement angle.…”
Section: Taguchi Analysis For Erosion Wearmentioning
confidence: 73%
“…The impingement angle, impact velocity, and erodent size are the most studied factors that significantly influence erosion behavior. It was well documented in the literature that erosion wear remains highest for ductile and brittle materials at low (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and high (90 ) impingement angles, respectively. [27] In comparison, erosion wear is found to increase with an increase in impact velocity and erodent size.…”
Section: Taguchi Analysis For Erosion Wearmentioning
confidence: 92%
See 1 more Smart Citation
“…Various artificial and natural porous materials having developed specific surface area are used to remove cations of toxic metal from aquatic media, including zeolites (Aljerf 2018), carbon-containing terpels (Shashkova et al 2001), dolomites (Sdiri 2018), and carbon sorbents based on vegetable and animal raw materials (Pakshirajan et al 2013;Elabbas et al 2015). When treating wastewater containing heavy metal ions, the main practical task is to select local materials that are of a low cost but effective.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hands, effluents discharge into municipal sewers by mining, metallurgy, electroplating, electronics, textile, nuclear, and other industrial effluents have become serious threats to the receiving environment. Therefore, controlling those effluents is of outmost importance (Yang et al 2013;Sdiri et al 2018;Sdiri 2018). A number of technologies have been developed for the removal and recovery of various pollutants including filtration, chemical precipitation, ion exchange, adsorption, electrodeposition, and membrane systems (Kesraoui et al 2016;Othmani et al 2017).…”
mentioning
confidence: 99%